Visual arts in Cameroon : a genealogy of non-formal training, 1976-2014 - Schemmel, Annette (Langaa Research & Publishing CIG, 2015)
Annette Schemmel provides a highly illuminating case study of the major actors, discourses and paradigm that shaped the history of visual arts in Cameroon during the second part of the 20th century. Her book meticulously reconstructs the multiple ways of artistic knowledge acquisition - from the consolidation of the "Systeme de Grands Freres" in the 1970s to the emergence of more discursively oriented small artists' initiatives which responded to the growing NGO market of social practice art opportunities in the 2000s. Based on archival research, participant observation and in depth interviews with art practitioners in Douala and Yaounde, this study is a must read for everyone who wants to better understand the vibrant artistic scenes in countries like Cameroon, which until today lack a proper state-funded infrastructure in the arts